Genomic perspectives on the birth and spread of plastids - Archibald, John M. (Proc Natl Acad Sci U S A, 2015)
The endosymbiotic origin of plastids from cyanobacteria was a landmark event in the history of eukaryotic life. Subsequent to the evolution of primary plastids, photosynthesis spread from red and green algae to unrelated eukaryotes by secondary and tertiary endosymbiosis. Although the movement of cyanobacterial genes from endosymbiont to host is well studied, less is known about the migration of eukaryotic genes from one nucleus to the other in the context of serial endosymbiosis. Here I explore the magnitude and potential impact of nucleus-to-nucleus endosymbiotic gene transfer in the evolution of complex algae, and the extent to which such transfers compromise our ability to infer the deep structure of the eukaryotic tree of life. In addition to endosymbiotic gene transfer, horizontal gene transfer events occurring before, during, and after endosymbioses further confound our efforts to reconstruct the ancient mergers that forged multiple lines of photosynthetic microbial eukaryotes.